Answer:
Equivalent expressions are expressions which are equal. This means they simplify to the same expression. Simplify the two expressions -1.3x - (-8.9x) = 7.6x and -1.3 + (-8.9X) = -10.2x.
Then simplify each option to determine if it is equal -1.3x - (-8.9x), -1.3 + (-8.9X) or neither:
−1.3x−8.9x = -10.2x. This is equivalent to -1.3 + (-8.9X) .
8.9x+(−1.3x) = 7.6x This is equivalent to -1.3x - (-8.9x) .
−8.9x+(−1.3x) = -10.2x This is equivalent to -1.3 + (-8.9X) .
8.9x−(−1.3x) = 10.2x Neither
−1.3x+8.9x = 7.6x This is equivalent to -1.3x - (-8.9x) .
−8.9x+1.3x = -7.6x Neither
Step-by-step explanation:
Answer:
(w^2 - 4w + 16)
Step-by-step explanation:
Note that w^3 +64 is the sum of two perfect cubes, which are (w)^3 and (4)^3. The corresponding factors are (w + 4)(w^2 - 4w + 16).
Therefore,
(w^3 +64)/(4+ w) reduces as follows:
(w^3 +64)/(4+ w) (4 + w)(w^2 - 4w + 16)
--------------------------- = --------------------------------- = (w^2 - 4w + 16)
4 + w 4 + w
Since the formula for the area of a circle is Pi x r squared, the area would be 81 x Pi (you teacher may want you to use Pi as 3.14 or put it in your calculator).
Answer:
x=-3 y=17 (-3;17)
Step-by-step explanation:
-3x+8-y=0
-5x+2-y=0
-2x-6=0
So: x=-3
While....by substituting: y=17